Research on the Impact of Digital Transformation on Enterprise ESG Rating Performance - Wu, Chenyang (Transactions on Economics, Business and Management Research, 2024)
Up against a new round of technological revolution, it has become an important strategic means for enterprises to accelerate digital development and promote the digital transformation of economic activities. Empirically testing the impact and mechanism of digital transformation of listed companies on ESG performance, this paper draws the following conclusions. Digital transformation of enterprises can significantly improve ESG performance, and the higher the quality of enterprises’ internal control, the more positive the effect of digital transformation on ESG performance. For non-state-owned enterprises, the positive impact of digital transformation on ESG performance is more significant. This article incorporates digital transformation and ESG performance into the same analysis framework, expands existing research, and puts forward corresponding suggestions and prospects.